The effects of viscosifiers on Terengganu k-shale hydration - Ismail, Abdul Razak; Ng, Chong Yeow (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Operational experience showed that drilling through reactive and sensitive shale formations will result in well bore instability problems. Borehole instability can result from erosion, swelling and dispersion of formation clays. It will cause many problems such as stuck pipe, high torque and drag, bridging and hole enlargement. In general, the well bore stability can be achieved by using oil-based drilling fluids. However, due to the environmental reasons, a need for a better understanding of drilling fluids and shale interaction are very important to formulate an environmental friendly drilling fluid. This study focused on the effects of selected viscosifiers and its concentrations on Terengganu K-shale hydration. The characteristics of K-shale was identified using methylene blue test (MBT). The effects of several viscosifiers such as xanthan gum, PAC-R, polyplus-dry and hydroxyl ethyl cellulose (HEC) on shale hydration were studied using hot-rolling dispersion test. The results showed that viscosifiers can be used to prevent shale hydration. Besides, an increase of viscosifiers concentration can reduce shale hydration and dispersion. The results also showed that xanthan gum and polyplus-dry are more efficient to prevent the shale hydration in comparison with the other two viscosifiers. The study also revealed that xanthan gum gives an optimum rheological properties of KCl-polymer system.